Communication Technologies and Tourism development in and around Nyungwe National Park, Rwanda. - Eugene, Kagayano (Kabale University, 2019)
A Research Report Submitted in Partial Fulfillment of the Requirements for the Award of Bachelors Degree in Tourism Management of Kabale University